MODELING INTENTION OF NOT USE MOBILE PHONE WHILE RIDING BASED ON THEORY OF PLANNED BEHAVIOR AND HEALTH BELIEF MODEL - Hayu Anindya, Alifia
The number of motorcyclists in Indonesia is increasing rapidly. Unfortunately, this number is directly proportional to the number of accidents experienced by motorcyclists. Various studies have proven that the use of mobile phones (mobile phones) is one of the causes of accidents that occur in motorcyclists. Therefore, further prevention efforts related to the use of mobile phones among motorcyclists are needed. The purpose of this study is to observe the behavior of mobile phone use in Bandung Raya and model factors that affect the intention of not to use mobile phones while riding. Total 500 of motorcyclists in Bandung Raya consisting of 388 men and 112 women, filled out questionnaires about demographic data, driving behavior, and questions related to the intention of not to use mobile phones while riding. Driving behavior is observed using the Theory of Planned of Behavior (TPB) and Health Belief model (HBM). TPB consists of Attitude, Subjective Norm, and Perceived Behavioral Control. HBM consisting of Perceived Benefit, Perceived Barrier, Perceived Severity, Perceived Susceptibility, and Cues to Action. Likert scale is used in responding to questions (1= strongly agree, 5= strongly disagree). The data is processed using descriptive statistical analysis and Structural Equation Modeling (SEM). The results showed that the prevalence of mobile phone use from respondents was 75%. Demographic that has significant impact on mobile phone use while motorcycling are age, education level, marital status, and child ownership. Occupation, gender, and accident experiences are less likely to affect cell phone use while motorcycling. Models show that factors that influence intention of not to use mobile phone while motorcycling are attitude, perceived behavioral control, and cues to action.